Bani Abbas dan Gerakan Nasionalisme Persia Klasik - Nurhasan Nurhasan (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
Pesian or Iranian experienced the glory in their political and social life for past decades. Then, with their primordial sentiments and national integration they kept trying to reach their previous glory. This process took placefor along time started by struggling to Omayyad until the appearance of Buwayhid.